2018
DOI: 10.3390/su10124793
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effect of Bacterial Inoculation and Fertilization on the Soil Nutrient Status of Coal Mine Soil by Growing Soybean (Glycine max) and Shrub Lespedeza (Lespedeza bicolor)

Abstract: Revegetation with fast-growing N-fixing leguminous plants can be an alternate for reclamation of degraded coal mining areas. Selection of appropriate plant species is an important factor in deciding the success in the remediation of mine spoil. Thus, this study was carried out in greenhouse conditions to evaluate the effect of two N-fixing leguminous plant seedlings, soybean (Glycine max) and shrub lespedeza (Lespedeza bicolor), on the available N and other soil nutrients (P, K, Ca, and Mg) of the experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…To estimate nitrogen fixation, we calculated the percent of nitrogen derived from air (% Ndfa). The estimated amount of fixed nitrogen is very rough because of the possibility for the influence of other soil microbes or inoculation on soil nutrient status, and thus on the intake of mineral forms of nitrogen [ 61 , 62 ]. Inoculation of chickpea with rhizobium strains MA72 or MA100 combined with M131 or P1S6 or P fertilizer resulted in a significantly higher % of nitrogen derived from air in both sites as compared to single inoculation with MA72 or MA 100 ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…To estimate nitrogen fixation, we calculated the percent of nitrogen derived from air (% Ndfa). The estimated amount of fixed nitrogen is very rough because of the possibility for the influence of other soil microbes or inoculation on soil nutrient status, and thus on the intake of mineral forms of nitrogen [ 61 , 62 ]. Inoculation of chickpea with rhizobium strains MA72 or MA100 combined with M131 or P1S6 or P fertilizer resulted in a significantly higher % of nitrogen derived from air in both sites as compared to single inoculation with MA72 or MA 100 ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, information about the composition of microbial communities that persist in mine substrates and how they might both influence and respond to mine rehabilitation, in its early stages, is still scarce. Inoculation of mine substrates with bacteria, to enhance rehabilitation, is being actively investigated, to improve plant productivity [ 17 19 ] post mine closure. However, few bacteria inocula can survive in mine substrates [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, inoculated treatment may add only a small concentration of NO 3 − -N to the soil through nodulation because of weak nodule formation. A previous study showed increase of NO 3 − -N in the coal mine soil through bacterial inoculation and fertilization when applied to soybean and shrub lespedeza plant [13].…”
Section: Effects Of Fertilization and Bacterial Inoculation On Nh 4 +mentioning
confidence: 98%
“…NH 4 + -N increased in a little amount at nonfertilized non-inoculated treatment without application of additional N, despite of using NH 4 + -N by developing plants for their growth, might be due to the mineralization of organic N present in the soil. Shin et al [13] reported increase of NH 4 + -N in the coal mine soil after 60 days of inoculation and fertilization, applied to shrub lespedeza and soybean. Cakmakci et al [14] also showed the same result in the soil of barley plant.…”
Section: Effects Of Fertilization and Bacterial Inoculation On Nh 4 +mentioning
confidence: 99%